2008
DOI: 10.1007/s00246-008-9242-z
|View full text |Cite
|
Sign up to set email alerts
|

What is the True Frequency of Carditis in Acute Rheumatic Fever? A Prospective Clinical and Doppler Blind Study of 56 Children with up to 60 Months of Follow-Up Evaluation

Abstract: Patients who had acute rheumatic fever without clinical signs of carditis showed acute and late follow-up echocardiographic abnormalities suggestive of cardiac involvement. Clinicians should be attentive for the presence of cardiac involvement among patients with chorea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…The frequency of carditis in the present study was found to be 66%, which is consistent with earlier investigations that reported rates of 40–80% . The mitral valve was the most commonly involved valve (93.2%) in the present study, followed by aortic valvulitis in 32% of cases.…”
Section: Discussionsupporting
confidence: 92%
“…The frequency of carditis in the present study was found to be 66%, which is consistent with earlier investigations that reported rates of 40–80% . The mitral valve was the most commonly involved valve (93.2%) in the present study, followed by aortic valvulitis in 32% of cases.…”
Section: Discussionsupporting
confidence: 92%
“…Recent Vanderbilt data suggest that most cases of ARF initially present with joint findings or chorea, reducing the need for front‐line practitioners to perform an in‐depth initial cardiological evaluation. A literature review incorporating studies performed across the globe from 1921 to 2008 corroborates these findings; Tables 3 and 4 summarize the literature review 5–14,16–18 . Studies from the USA found that greater than 75% of new ARF cases presented with joint manifestations or chorea, while data from international sites indicated that 55–100% of cases had similar findings.…”
Section: Discussionmentioning
confidence: 64%
“…With regard to color-Xow mapping, appropriate gain and pulse repetition frequency settings were used, and the following aspects were taken into account: mitral regurgitation was considered to be present if blue, green, or mosaic signals were seen originating from the mitral valve and spreading into the left atrium during systole. Aortic regurgitation was considered to be present if red, yellow, or mosaic signals were seen originating from the aortic valve and spreading into the left ventricle during diastole [9]. The degree of mitral regurgitation was measured by the relationship between maximal jet areas corrected for the atrial area.…”
Section: Echocardiography Doppler Examinationmentioning
confidence: 99%